PEMANFAATAN ABU SEKAM PADI SEBAGAI SUBSTITUSI SEBAGIAN SEMEN PADA MORTAR SEMEN PASIR - MUHTAROM RIYADI (Jurnal Poli-Teknologi, 2013)
ABSTRACT Tilization of waste from the combustion of rice husk ash bricks optimally, can solve the problem of environmental pollution. It also can save the construction costs due to reducing in the use of cement. The addition of fine grains that pass the sieve on the size of 0.075 mm can improve the workability of mortar, minimum the voids and finally waterproof ability improve strength. This studi is to determine the performance of rice husk ash on the physical and mechanical properties of mortar. Workability includes the water absorption,ability compressive strength, tensile strength, adhesion of the mortar and optimal percentage value addition of rice husk ash. The research method used in this research was a run by analising a series of samples experiments. The test piece was made with five kinds of mixtures, they were : 1 cement : 5 sand as a comparison and: 1 cement : 5 sand with rice husk ash substitution of cement by 10%, 15%, 20% and 25%, the water factor (cement + rha) between 0.92 to 1.05 and the value spread between 80% - 90% for each test specimen made 25 pieces. Every type of mixture was tested was : the spread, water absorption, compressive strength, tensile strength and bonding strength. The results showed that the addition proportionaly substitution rha composed with addition of water, and inversely composed to the density, the compressive strength, tensile strength, due to a chemical reaction of sio 2 and cao, rice ash husk only serves as a filler since the reaction was take place after 4 days old of sample. Compressive strength of mortar ranged from 10.25 mpa -13.00 mpa, including the type s mortar, for the substitution asp 0%, 10% and 15% asp, and type n for substitution asp 20% and 25% (sni-03-6882 -2002). Bonding strength of mortar was 0.09 mpa (0.9 kg/cm2) at 25% has substitution of asp, while others were not measurable because the specimen were bricks broken, before the bonding between the bricks was loose. Keywords: mortar, rice husk ash, physical and mechanical properties